2018
DOI: 10.1111/gfs.12353
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of milk yields and methane production from three contrasting high‐yielding dairy cattle feeding regimes: Cut‐and‐carry, partial grazing and total mixed ration

Abstract: There have been reductions in grazing cattle and corresponding increases in mixed diets across many regions. Mixed diets consist of silage, grains, legumes and other herbaceous plants (termed total mixed ration, TMR). TMR has been associated with increased milk yields but has also been linked to increased enteric methane production. We measured milk yields and methane production from high‐yielding Holstein‐Friesian cattle after substituting 29%–36% of a TMR diet with grass. Two feeding treatments were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
1
15
0
4
Order By: Relevance
“…As expected, increased butterfat percentage is positively related to technical efficiency; however, it does not have a significant effect on environmentally adjusted technical efficiency. The nonsignificance for environmentally adjusted technical efficiency may be at least in part because of the lack of availability of detailed nutrition management information in the data set (e.g., forage quality, use of mixed rations) and the potential importance of these factors in explaining methane emissions (e.g., Cameron et al, 2018;Eckard, Grainger, and de Klein, 2010). Years of farming (i.e., experience) is negatively related to technical efficiency.…”
Section: Inefficiency Modelmentioning
confidence: 99%
“…As expected, increased butterfat percentage is positively related to technical efficiency; however, it does not have a significant effect on environmentally adjusted technical efficiency. The nonsignificance for environmentally adjusted technical efficiency may be at least in part because of the lack of availability of detailed nutrition management information in the data set (e.g., forage quality, use of mixed rations) and the potential importance of these factors in explaining methane emissions (e.g., Cameron et al, 2018;Eckard, Grainger, and de Klein, 2010). Years of farming (i.e., experience) is negatively related to technical efficiency.…”
Section: Inefficiency Modelmentioning
confidence: 99%
“…LG. Bijvoorbeeld, vergelijkingen tussen TMR systemen (stalvoedering met ruwvoer) en weidegang laten een hoger gemiddeld LG zien bij TMR systemen dan bij weidegang (Fontaneli et al, 2005;O'Neill et al, 2011;Hofstetter et al, 2014;O'Callaghan et al, 2016;Cameron et al, 2018;Frey et al, 2018 Koeien nemen ook gedurende de derde lactatie (Koenen et al, 1999) en latere lactaties (Zom, 2014) nog in gewicht toe. De gewichtstoename is deels te verklaren door een hogere voeropname en grotere vulling van het maagdarmkanaal als gevolg van een grotere voeropnamecapaciteit.…”
Section: Voeropname Volgens De Bex Systematiekunclassified
“…Some research shows a reducing potential of both partial grazing and cut-and-carry on both CH4 yield and CH4 intensity. Cameron et al (2018) found reductions of CH4 production of 17% (cut-and-carry) and 39% (partial grazing) when around 33% of the total mixed ration diet was replaced with fresh grass. The percentage of fresh grass in the diet did not explain any of the observed variation in enteric CH4 intensity in this inventory.…”
Section: The Effect Of Fresh Grassmentioning
confidence: 96%